Bull Spermatozoa Morphometry Characteristic on Different Breeds and Ages - Gebrina, Deanne Putri; Hendri, Hendri; Masrizal, Masrizal (Universitas Bengkulu, 2024)
This study was conducted to determine the morphometric characteristics of bull spermatozoa of different breeds and ages. This study used a Completely Randomized Design with a Factorial pattern with factor A consisting of A1 (Simmental bull) and A2 (Limousin bull), and factor B consisting of B1 (2-4 years), B2 (5-7 years), and B3 (8-10 years). The variables observed in this study included the area of the spermatozoa head, length of the spermatozoa tail, and size of the spermatozoa body. This study's findings indicate an interaction (p < 0.05) between the breed and age of the bull on the area of ​​the spermatozoa head. Still, there is no interaction between the breed and age of the bull on the length of the spermatozoa tail and the size of the spermatozoa body. This study shows that Simmental bulls have higher spermatozoa morphometric characteristics than Limousin bulls. The results of the study of spermatozoa morphometric characteristics showed that the highest spermatozoa head area was in Limousin bull aged 5-7 years, namely 35.79 ± 3.91 µm2, the highest spermatozoa tail length was in Simmental bull aged 5-7 years, namely 49.28 ± 2.38 µm, the highest spermatozoa body length was in Simmental bull aged 5-7 years, 73.02 ± 4.32 µm. The findings of this study indicate that morphometric characteristics increased at the age of 5-7 years and decreased again at the age of 8-10 years.